Changes in the superior longitudinal fasciculus and anterior thalamic radiation in the left brain are associated with developmental dyscalculia - Ayyıldız, Nazife; Beyer, Frauke; Üstün, Sertaç; Kale, Emre H.; Mançe Çalışır, Öykü; Uran, Pınar; Öner, Özgür; Olkun, Sinan; Anwander, Alfred; Witte, A. Veronica; Villringer, Arno; Çiçek, Metehan (Frontiers in Human Neuroscience, 2023)
Developmental dyscalculia is a neurodevelopmental disorder specific to arithmetic learning even with normal intelligence and age-appropriate education. Difficulties often persist from childhood through adulthood. However, the neural correlates of developmental dyscalculia are poorly understood. This study aimed to identify brain structural connectivity alterations in developmental dyscalculia. All participants were recruited from a large-scale, non-referred population sample in a longitudinal design. We studied 10 children with developmental dyscalculia (11.3 ± 0.7 years) and 16 typically developing peers (11.2 ± 0.6 years) using diffusion-weighted magnetic resonance imaging. We assessed white matter microstructure with tract-based spatial statistics in regions of interest tracts that had previously been related to math ability in children. Then we used probabilistic tractography for the first time to measure and compare tract length between developmental dyscalculia and typically developing groups. The high angular resolution diffusion-weighted magnetic resonance imaging and crossing-fiber probabilistic tractography allowed us to evaluate the length of the pathways compared to previous studies. The major findings of our study were reduced white matter coherence and shorter tract length of the left superior longitudinal/arcuate fasciculus and left anterior thalamic radiation in the developmental dyscalculia group. Furthermore, the lower white matter coherence and shorter pathways tended to be associated with lower math performance. These results from the regional analyses indicate that learning, memory, and language-related pathways in the left hemisphere might be related to developmental dyscalculia in children.